2019
DOI: 10.3389/fendo.2019.00835
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics-Based Signaling Pathway Network Alterations in Human Non-functional Pituitary Adenomas

Abstract: Non-functional pituitary adenoma (NFPA) seriously affects hypothanamus-pituitary-target organ axis system, with a series of molecule alterations in the multiple levels of genome, transcriptome, proteome, and post-translational modifications, and those molecules mutually interact in a molecular-network system. Meta analysis coupled with IPA pathway-network program was used to comprehensively analyze nine sets of documented NFPA omics data, including NFPA quantitative transcriptomics data [280 differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 70 publications
3
42
1
Order By: Relevance
“…This result indicated that AKT1 was a DEG at the level of transcriptome, but it was not a DEP at the level of proteome, between NFPAs and controls. It might be derived from different protein PTMs to produce different AKT1 proteoforms (65)(66)(67)(68), which was confirmed by our another PTMScan experimental study that the phosphorylation levels at residues Ser473, Thr308, or Thr312 in AKT1 were significantly increased by at least 3 folds in NFPAs compared to controls (62). Therefore, the phosphorylated AKT1 (pAKT1) might contribute to NFPA pathogenesis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This result indicated that AKT1 was a DEG at the level of transcriptome, but it was not a DEP at the level of proteome, between NFPAs and controls. It might be derived from different protein PTMs to produce different AKT1 proteoforms (65)(66)(67)(68), which was confirmed by our another PTMScan experimental study that the phosphorylation levels at residues Ser473, Thr308, or Thr312 in AKT1 were significantly increased by at least 3 folds in NFPAs compared to controls (62). Therefore, the phosphorylated AKT1 (pAKT1) might contribute to NFPA pathogenesis.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, this study used western blotting analysis to confirm that the expression of AKT1 protein in NFPA and control tissues although it was not changed significantly between NFPAs and controls. However, in our research group, another study found phosphorylated AKT1 in NFPA was significantly increased (62), which might lead to the activation of PI3K-AKT-mTOR pathway. In addition, studies also showed that low levels of APAF-1 were inversely related to invasiveness, and cathepsin B expression was positively related to invasiveness in pituitary adenomas (63).…”
Section: Discussioncontrasting
confidence: 50%
“…Knock-down of FGD4 in PC-3 and LNCaP-104S prostate cell lines inhibited cell proliferation, cell cycle progression, and cell migration [60]. In pituitary adenoma, ARHGAP18 and ARHGEF17 are both upregulated, suggesting a modulation of the activity of the target Rho GTPases, most likely RhoA [44]. Variation in VAV isoforms (GEFs for Rho and Rac GTPases) expression levels was reported in small cell lung carcinoma [62,63].…”
Section: Control Of Rho Activity In Nets: Important Role Of Rho Gefsmentioning
confidence: 98%
“…However, only a few studies were performed in NETs, mainly in pituitary adenoma and neuroblastoma, as well as in tumors from the thyroid, parathyroid, and small cell lung. For instance, in pituitary adenoma, Rac1 overexpression and Cdc42 down-regulation may affect pathways controlling tumorigenesis such as mTOR-and Wnt-signalling pathways [44]. Arising from primitive cells of the sympathetic nervous systems, neuroblastoma is a common childhood extracranial solid tumor with neuroendocrine properties [45].…”
Section: Neuroendocrine Tumors and Rho Gtpasesmentioning
confidence: 99%
“…Despite intensive molecular investigations, mechanisms of pathogenesis of NFPA are not completely understood [ 22 , 23 ]. However, evidence suggests that high levels of expression of β-CATENIN protein contribute to the development of NFPA [ 24 , 25 ].…”
mentioning
confidence: 99%